Histological Changes Observed in Placentas Exposed to Medication-Assisted Treatment. (7th October 2021) - Staszewski, Cara; Herrera, Kimberly M.; Kertowidjojo, Elizabeth; Ly, Victoria; Iovino, Nicole; Garretto, Diana; Kaplan, Cynthia; Persad, Malini D.; Garry, David J.
Abstract : Introduction . To compare the effects of medication-assisted treatment on the placenta in pregnant women with opioid use disorder and uncomplicated pregnancies. Methods . This is a case-controlled study of pregnant women utilizing medication-assisted treatment, buprenorphine or methadone, which were matched to healthy uncomplicated controls by gestational age. Placental evaluations and neonatal outcomes were evaluated. Data analysis performed standard statistics and relative risk analysis with a p < 0.05 considered significant. Results . There were 143 women who met the inclusion criteria: 103 utilizing MAT, 41 buprenorphine and 62 methadone, and 40 uncomplicated matched healthy controls. The incidence of delayed villous maturation was 36% in the medication-assisted group compared with 10% in controls (RR 3.6: 95% CI 1.37-9.43; p < 0.01 ). The placental weight was greater (541 ± 117 g versus 491 ± 117 g; p = 0.02 ), and the fetoplacental weight ratio was lower (5.70 ± 1.1 versus 7.13 ± 1.4 ; p < 0.01 ) in the medication-exposed pregnancies compared with controls. The mean birth weight of the MAT newborns was significantly lower than that of the healthy controls (3018 ± 536 g versus 3380 ± 492 g; p < 0.01 ). When evaluating the subgroups of the MAT newborns, the birth weight of the methadone-exposed newborns (2886 ± 514 g) was significantly lower than that of the buprenorphine-exposed newborns (3218 ± 512 g; p < 0.01 ). Conclusion . Medication-exposed pregnancies have a greater incidence of delayed villous maturation, a larger placental size, and a decreased fetoplacental weight ratio compared to the healthy controls. Larger long-term follow-up studies to evaluate outcomes with the presence of delayed villous maturation are needed.